1997
DOI: 10.1046/j.1365-313x.1997.12040911.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and environment interact to control dormancy and differential expression of the VIVIPAROUS 1 homologue in embryos of Avena fatua

Abstract: SummaryEmbryo dormancy is a reversible developmental state during which germination is repressed. In this study, inbred lines of Avena fatua were used to analyse the influence of genotype and environment on the dormant phenotype, and on expression of the homologue of the maize transcription factor VIVIPAROUS 1 (afVP 1). The cDNA for afVP 1 was cloned from mature embryos. Analysis of the predicted protein sequence revealed a high degree of similarity to other VP 1/ABI 3-related transcription factors, in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 21 publications
2
70
0
4
Order By: Relevance
“…The Viviparous 1 family of transcription factors has been shown previously to be highly conserved in flowering plants (5,6). We used the Avena fatua orthologue (AfVp1) as a probe to identify Vp-1 transcripts in mature wheat embryos (data not shown) and to clone cDNAs representing TaVp1 mRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Viviparous 1 family of transcription factors has been shown previously to be highly conserved in flowering plants (5,6). We used the Avena fatua orthologue (AfVp1) as a probe to identify Vp-1 transcripts in mature wheat embryos (data not shown) and to clone cDNAs representing TaVp1 mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Other evidence shows that ABA levels in embryos are similar in both sprouting sensitive and resistant cultivars and that sprouting behavior is more related to the extent of ABA responsiveness of embryos (36). Analysis of transgenic wheat embryos showed that dormancy levels measured as increased ABA responsiveness could be manipulated via expression of the Vp1 orthologue AfVp1, previously implicated in the regulation of the high levels of embryo dormancy in A. fatua (5). As predicted from vp1 and abi3 mutant studies, inhibition of germination of AfVp1 transgenic wheat embryos is more responsive to ABA than the control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gain of desiccation tolerance of orthodox seeds during their development has been correlated to different expression of genes such as ABI3, ABI5, LEC1 (Jones et al, 1997;Koornneef et al, 1984;Parcy et al, 1994;Harada, 2001), among others. The genes LEC (Leafy cotyledon) are defined by mutations in three loci in Arabidopsis, LEC1,LEC2 and FUSCA3 (FUS3) and are mainly involved on the embryo development (Harada, 2001).…”
Section: Introductionmentioning
confidence: 99%